Synthetic and Mechanistic Investigations of the Chemistry of a α-Substituted Diazenes - McCallion, J. (My University, 1986)
It had been proposed that α-hydroperoxydiazenes decompose by the radical chain abstraction of the hydroxy group. This suggested that these compounds could be used as hydroxyalkylating agents for unsaturated systems.
Compounds 15 and 23 were prepared by the autoxidation of the corresponding hydrazone. α-Hydroperoxydiazenes 15 and 23 were used to hydroxyalkylate ethyl vinyl ether and 2-methoxypropene in yields of 62-65%. Mechanisms of the addition reaction are discussed.
In an attempt to alkylate a hetero atom system, ·compound 15 was thermolyzed with compound 25. The alkylation product was not obtained.
Compound 15 was converted to α-hydroxydiazene 34 by the action of Φ3P. α-Hydroxydiazine have been used synthetically in the hydroalkylation of alkenes. The rate constant of hydrogen abstraction was determined to be in the range of 1.5 x 10^5 M^-ls^-l to 1.5 x 10^7 M^-ls^-l by the use of a radical clock reaction. An upper limit on the rate of rearrangement of the 2-cyanopropyl radical was found to be 3.65 x 10^3 s^-1 .
A new compound (23) was prepared
Keywords: α-Substituted Diazene; mechanistic investigation; chemistry; hydroperoxydiazenes